Me or just like me? The role of virtual try-on and physical appearance in apparel M-retailing. (November 2019) - Plotkina, Daria; Saurel, Hélène
Abstract: This research investigated a crucial topic in apparel m-commerce: product presentation and the extent to which it should exhibit human visuals corresponding to consumers' appearance. A mobile application with virtual try-on (VTO) tool based on augmented reality was compared to a traditional m-commerce interface showing models with physical features not, partially, or completely similar to the consumers'. A theoretical framework based on the Technology Acceptance Model was adopted to explain the impact of the application and the mediating role of perceived hedonic value (enjoyment) and utilitarian value (convenience, ease of use, and usefulness) on attitude toward the shopping technology and purchase intention. An online experiment (415 respondents) and a qualitative study (49 respondents) showed that the VTO tool was less enjoyable than traditional m-commerce interfaces and less convenient and useful than pictures of models with physical features similar to those of consumers. Implications for academics and managers are discussed.